2010
DOI: 10.1016/j.bpc.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Excited protein states of human tear lipocalin for low- and high-affinity ligand binding revealed by functional AB loop motion

Abstract: Human tear lipocalin (TL), a prominent member of lipocalin family, exhibits functional and structural promiscuity. The plasticity of loop regions modulates entry to the ligand pocket at the "open" end of the eight-stranded β-barrel. Site directed multi-distance measurements using fluorescence resonance energy transfer between functional loops register two excited protein states for low-and high-affinity ligand binding. At low pH, the longest loop AB adopts the conformation of the lowaffinity excited protein st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 64 publications
(124 reference statements)
2
16
0
Order By: Relevance
“…Unlike other lipocalins, TL shows significant conformational changes in the apo- to holo transition. 25 , 26 , 48 , 49 Accordingly, the position 124 shows marked displacement (4.90 Å) in the α-helix upon ligand binding (Figure 9 ). This suggests that the N-terminus residue, W124, is conformationally mobile to sample multiple conformations and is reflected in greater CD augmentation compared to other sites of the α-helix.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike other lipocalins, TL shows significant conformational changes in the apo- to holo transition. 25 , 26 , 48 , 49 Accordingly, the position 124 shows marked displacement (4.90 Å) in the α-helix upon ligand binding (Figure 9 ). This suggests that the N-terminus residue, W124, is conformationally mobile to sample multiple conformations and is reflected in greater CD augmentation compared to other sites of the α-helix.…”
Section: Discussionmentioning
confidence: 98%
“…7, Table 2). Recombinant tear lipocalin has been taken as a surrogate for the apo-form without exposure to solvents for delipidation [19,55]. During expression tear lipocalin binds some lipids, but fewer than native tear lipocalin [56,57].…”
Section: Influence Of Delipidation On Assessment Of the Stoichiometrimentioning
confidence: 99%
“…The conformation of Trp28 is driven by protonation states of the neighboring residues and is stabilized by ligand binding. Moreover, the distance measurements using FRET method have indicated that in the pH induced transition, Trp28 (originally Phe28) was moved, 4.5 Å, toward the loop EF (14). This result obtained in solution is concord with the crystal structures of TL in apo- and holo-forms (15, 30).…”
Section: Discussionmentioning
confidence: 99%
“…Human tear lipocalin (TL), also known as von Ebner's gland protein, is an archetypical ligand binding member of the lipocalin family (11). The enhanced promiscuity of TL for lipids is derived from structural plasticity and a large mouth as determined by site-directed tryptophan fluorescence (SDTF) (1214). X-ray crystallography of TL is concordant with the SDTF derived solution structure (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation